100(x-3)=450-5x

Simple and best practice solution for 100(x-3)=450-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 100(x-3)=450-5x equation:


Simplifying
100(x + -3) = 450 + -5x

Reorder the terms:
100(-3 + x) = 450 + -5x
(-3 * 100 + x * 100) = 450 + -5x
(-300 + 100x) = 450 + -5x

Solving
-300 + 100x = 450 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-300 + 100x + 5x = 450 + -5x + 5x

Combine like terms: 100x + 5x = 105x
-300 + 105x = 450 + -5x + 5x

Combine like terms: -5x + 5x = 0
-300 + 105x = 450 + 0
-300 + 105x = 450

Add '300' to each side of the equation.
-300 + 300 + 105x = 450 + 300

Combine like terms: -300 + 300 = 0
0 + 105x = 450 + 300
105x = 450 + 300

Combine like terms: 450 + 300 = 750
105x = 750

Divide each side by '105'.
x = 7.142857143

Simplifying
x = 7.142857143

See similar equations:

| -2(x-3)=0 | | -2(7a-6)+3a=45 | | 3x+5=5x-15 | | 3x+2(x-7)=-59 | | 2+3*3+4*4+5=65 | | 12x-85=6x+83 | | 12k+13=25 | | 4X+(7Y-12)=180 | | 11-3k=32 | | 2x^2+3x+12=0 | | 5.24=5y+3.89 | | 5+1*2+4=36 | | 8a+9+5=-25 | | 2+6x=8+2x | | 12-7k=-2 | | 9m-6(-4m+2)= | | 4r^2-36r+56= | | 6l-9=15 | | 3-2*5+9=-4 | | 3t-12=2t+1 | | 2k+10=-12 | | 4x+2(4-(2x+4))=2x | | x^2-3x^3-14x^2-3x+40=0 | | 5y+4=4y+4 | | 5m-7=6m-29 | | 6+2*5+9=49 | | 10j-19=11 | | x^4-x^2=12x^2+48 | | 5+5x=6+2x | | 4l+20=0 | | 6+2*5+=49 | | 21=-6+3(z-5) |

Equations solver categories